The Influence of Work Environment and Organizational Communication on Employee Performance Through Job Satisfaction as a Mediation in Savings and Loan Cooperatives in Tanah Lot Tabanan Bali - I Gusti Ngurah Agung Wisnu WARDANA; I Made Suniastha AMERTA; I Wayan Gde SARMAWA (International Journal of Environmental, Sustainability, and Social Science, 2025)
A common issue in Indonesian cooperatives is poor coordination and communication among employees. Routine and annual member meetings often do not run effectively, leading to minimal business activity and transaction flows due to low member participation. Effective communication and coordination are essential for any organization, including cooperatives, yet available digital technologies remain underutilized. Management plays a crucial role in organizing and supervising employees to enhance professionalism and discipline. A supportive work environment, clear regulations, and strong workplace relationships are necessary for optimizing employee performance and adaptability. Increased productivity directly correlates with improved performance. This study analyzes the impact of the work environment and organizational communication on employee performance, with job satisfaction as a mediating factor in savings and loan cooperatives in Tanah Lot, Tabanan, Bali. The study population includes 150 employees from five cooperatives: Dwi Guna, Gunung Tegaljaya, Dana Mulya Jaya Lestari, KSP Karidana, and Kerta Yuga. Using proportional random sampling with the Slovin formula, 110 employees were selected. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). Results show that the work environment and organizational communication positively and significantly affect job satisfaction and employee performance. Job satisfaction also significantly impacts performance and mediates the relationships between both work environment and communication with employee performance. These findings emphasize the importance of fostering a positive work environment and effective communication to enhance job satisfaction and performance in cooperatives.